Preparation and performance of UiO‐66‐(COOH)2‐based mixed matrix membranes for efficient separation of Sr2+ ions from aqueous solutions. Issue 5 (15th February 2023) - Chen, Minjuan; Zeng, Jianxian; Wu, Zhenwei; Zhang, Rui; Yuan, Zhengqiu; Huang, Xiaoping; Jin, Kai; Yang, Shengkai; Li, Yahong
Abstract: BACKGROUND: Developing new materials for separating Sr 2+ ions from aqueous solutions is significant. Metal–organic frameworks are regarded as excellent adsorption materials due to their high specific surface area and abundant adsorption sites. In this work, a novel UiO‐66‐(COOH)2 ‐based mixed matrix membrane (MMM) was prepared by combining UiO‐66‐(COOH)2 with polyethersulfone (PES) for separating Sr 2+ . RESULTS: The MMMs were characterized using scanning electron microscopy, Fourier transform infrared spectroscopy and water contact angle and water flux measurements. Various contents (0–2.5 wt%) of UiO‐66‐(COOH)2 were blended into PES membranes. The results showed that incorporating UiO‐66‐(COOH)2 significantly increased membrane porosity and water flux, and reduced contact angle. The membrane (M4) that contained 2.0 wt% UiO‐66‐(COOH)2 exhibited an excellent morphology and the highest Sr 2+ uptake capacity (111.9 μg cm −2 ). Adsorption kinetics and isotherms showed that the nature of the adsorption of the membrane towards Sr 2+ was chemisorption, homogeneous and monolayer. Compared with the adsorption capacity of UiO‐66‐(COOH)2 towards Sr 2+ in adsorption packed column, these values of M4 decreased by about 75% during membrane filtration. The rejection performance of MMMs increased with increasing UiO‐66‐(COOH)2 content. Breakthrough curves of MMMs were not correlated with flow rate in the range of 10–180 mL h −1 . The presence of Ca 2+ and Mg 2+ ions did not obviously affect the separation of Sr 2+, but Pb 2+ had a significant influence. Furthermore, after five adsorption–desorption experiments, the regeneration remained at about 95% of initial values. CONCLUSIONS: The MMMs showed good adsorption capacity for Sr 2+ and exhibited favorable reusability and stability. © 2023 Society of Chemical Industry (SCI).